2012
DOI: 10.1186/1471-2407-12-533
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution of human papillomavirus (HPV) in histological sections of cervical intraepithelial neoplasia and invasive cervical carcinoma in Madrid, Spain

Abstract: BackgroundHuman Papillomavirus (HPV) genotype distribution and co-infection occurrence was studied in cervical specimens from the city of Madrid (Spain), as a contribution to the knowledge of Human Papillomavirus genotype distribution and prevalence of carcinogenic HPV types in cervical lesions in Spain.MethodsA total of 533 abnormal specimens, from the Hospital General Universitario “Gregorio Marañón” of Madrid, were studied. These included 19 benign lesions, 349 cervical intraepithelial neoplasias 1 (CIN1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
4
15
2
Order By: Relevance
“…The overall prevalence of any HPV in SCC samples was 92.2% and was 68.0% across all cervical samples investigated. HR‐HPV was detected in 64.8% of all samples with HPV‐16 being the most common HPV genotype identified, which is consistent with that described elsewhere in CIN cases across Europe in countries such as Spain, France, and Germany [García‐Espinosa et al, ; Monsonego et al, ; de Jonge et al, ; Leinonen et al, ; Rössler et al, ] and in invasive disease internationally [Bosch et al, ; de Sanjose et al, ; Li et al, ]. As previously reported the prevalence of HPV increased through CIN I–III lesions in NI [Anderson et al, ] from 48.1% in CIN I to 81.3% in CIN III cases.…”
Section: Discussionsupporting
confidence: 87%
“…The overall prevalence of any HPV in SCC samples was 92.2% and was 68.0% across all cervical samples investigated. HR‐HPV was detected in 64.8% of all samples with HPV‐16 being the most common HPV genotype identified, which is consistent with that described elsewhere in CIN cases across Europe in countries such as Spain, France, and Germany [García‐Espinosa et al, ; Monsonego et al, ; de Jonge et al, ; Leinonen et al, ; Rössler et al, ] and in invasive disease internationally [Bosch et al, ; de Sanjose et al, ; Li et al, ]. As previously reported the prevalence of HPV increased through CIN I–III lesions in NI [Anderson et al, ] from 48.1% in CIN I to 81.3% in CIN III cases.…”
Section: Discussionsupporting
confidence: 87%
“…We found no significant link between the histological lesions and the HPV carrier. In our study, the prevalence rate of precancerous lesions was significantly lower than that of most studies [13] [15] [21]. This could be explained by the size of our sample but especially by the quality of our samples; or other factors other than HPV such as bacteria, parasites, fungi, other virus, or simply other HPV genotypes that our detection kit could not characterize.…”
Section: Discussioncontrasting
confidence: 74%
“…Garcia-Espinosa et al found 18.4% of multiple infections. [21] In South Africa, 24% of cases of multiple infections were observed [18]. In Burkina Faso, 78.03% of cases of multiple infections were observed, but 90.1% of the patients were HIV-infected [10].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, the incidences of particular HR-HPV infections were observed to increase in association with the severity of the cervical intraepithelial neoplasia in the present study (5,35,42,43). In previous studies, each high-grade cervical neoplasia was attributed to a single HR-HPV infection, and HPV16 and 31 were the predominant HR-HPV types (44). These results are similar to the cytological findings of the present study, which demonstrated that the most frequent HPV types were HPV16 and 31.…”
Section: Discussionsupporting
confidence: 69%